ANALISIS KEMAMPUAN KUALITAS AUDITOR MEMODERASI PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Evangelista; Suhartono, Sugi (Jurnal Akuntansi, 2024)
The long-term goal of a company is to increase the value of the company. If the company’s financialperformance increases, the value of the company will also increase and vice versa. However, in reality, financial performance does not always move in tandem with company value. As happened in several state-owned companies. This study aims to determine the effect of financial performance on firm value which will then be moderated by auditor quality The objects of this research are 21 non-financial BUMN companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique in this study was purposive sampling. Data testing carried out in this study was descriptive analysis test, pooling test, classic assumption test, regression analysis test with Moderated Regression Analysis and hypothesis testing with SPSS version 26 program. The rusults of the research it was concluded that profitability has a positive effect on firm value. Liquidity has a negative effect on firm value. Solvability has no effect on firm value. Auditor quality is not able to strengthen the positive effect of profitability on firm value. Auditor quality is not able to strengthen the negative effect of liquidity and solvency on firm value.